2016
DOI: 10.3390/v8050131
|View full text |Cite
|
Sign up to set email alerts
|

Protein 2B of Coxsackievirus B3 Induces Autophagy Relying on Its Transmembrane Hydrophobic Sequences

Abstract: Coxsackievirus B (CVB) belongs to Enterovirus genus within the Picornaviridae family, and it is one of the most common causative pathogens of viral myocarditis in young adults. The pathogenesis of myocarditis caused by CVB has not been completely elucidated. In CVB infection, autophagy is manipulated to facilitate viral replication. Here we report that protein 2B, one of the non-structural proteins of CVB3, possesses autophagy-inducing capability. The autophagy-inducing motif of protein 2B was identified by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…In HCV-infected cells, NS3/4A blocks the RIG-I signaling pathway in the early stages of autophagy and modulates the binding of mitochondria-associated immunity-associated GTPase family M (IRGM) to promote autophagy [43]. Similarly, JEV NS3 targets IRGM to modulate autophagy [44], and CBV2 protein 2B, whose C-terminal sequence plays a decisive role in autophagy, rearranges the cell membrane [45]. In our study, GFP-LC3 puncta accumulated in Nsp3-mCherry-, Nsp5-mCherry-and Nsp9-mCherry-transfected cells and p62 expression was increased, indicating that NSP3, NSP5 and NSP9 induced the formation of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In HCV-infected cells, NS3/4A blocks the RIG-I signaling pathway in the early stages of autophagy and modulates the binding of mitochondria-associated immunity-associated GTPase family M (IRGM) to promote autophagy [43]. Similarly, JEV NS3 targets IRGM to modulate autophagy [44], and CBV2 protein 2B, whose C-terminal sequence plays a decisive role in autophagy, rearranges the cell membrane [45]. In our study, GFP-LC3 puncta accumulated in Nsp3-mCherry-, Nsp5-mCherry-and Nsp9-mCherry-transfected cells and p62 expression was increased, indicating that NSP3, NSP5 and NSP9 induced the formation of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the hydrophobic motif ser 662 is an essential step in the activation of the cell survival and death regulation protein protein kinase C delta (PKCd) (53). The transmembrane hydrophobic sequences of CVB non-structure protein 2B is essential for the induction of autophagy (54). In view of this, we firstly predict the hydrophobic property of FMDV, PV and SVA proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that some viruses, including polio virus [26], hepatitis C virus [27,28], dengue virus [29,30] can induce autophagy. Coxsackie virus can either inhibit autophagy or induce the formation of autophagosomes to increase viral replication [31,32]. Xi and the colleagues determined autophagy was induced by EV71 virus in RD-A cells, with an increase in the time course of infection (6h, 9h, 12h and 24h) by EV71, the conversion of LC3-I to LC3-II and the degradation of p62 increased accordingly [7].…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection could induce autophagy, and many viral proteins can induce autophagy also [37][38][39][40]. A recent study showed that neither 2B, 2C, 3A, 3B, 3AB, 3C nor 3D could trigger autophagy individually [7].…”
Section: Discussionmentioning
confidence: 99%